Pengembangan “Desa Wisata Kampung Koi” Latukan sebagai Upaya Penguatan BUMDesa melalui Pengembangan Kelompok Pembudidaya dan BUMDesa Latukan, Kabupaten Lamongan: Empowerment of Latukan "Koi Village" as an Effort to Strengthen BUMDesa through the Development of Fish Farmers and BUMDesa Latukan Village, The Regency of Lamongan - Maftuch, Maftuch; Setyawan, Fahreza Okta; Astuti, Retno Tri; Farikhah, Reghita Dwi; Ash Shufi, Abdillah Hanan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Latukan Village is one of the villages in Lamongan Regency with Independent Village status in the 2020 Building Village Index (IDM). Independent Village has the highest status in the IDM assessment scale published by the Ministry of Villages. Through the  Empowered Village Program, Latukan Village seeks to build a village icon by constructing the Latukan “Koi Village”. However, the complete design concept regarding the development of Latukan Village as a  Kampung Koi Tourism Village has not yet been formed optimally. Therefore, it is essential to prepare strategic development steps, which include elements of Koi Fish Cultivation, Post-harvest Management, Transportation, Marketing Management, the establishment of recreational and educational parks, as well as human resource development, in this case, the Koi Fish Cultivator Group and the Harvest Management Group. The solution is to create a development design for the Kampung Koi Tourism Village as part of the BUM Desa business unit. For this reason, the Brawijaya University Community Service team designed an activity to build a stronger and more sustainable Latukan Village Icon. Service activities consist of identifying the status of the problem and planning solutions, forming a koi fish cultivator group and making portable spawning ponds, strengthening the role of BUMDesa, village government, and cultivators through focus group discussions and comparative studies, and koi fish cultivation and breeding training. All activities have been conducted and compiled in scientific publications and mass media. In its implementation, this activity involved five students concentrating on fisheries cultivation and fishery product technology.